Distribution of protected area and large-sized mammals order in Ethiopia - Tamirat, Haile Chankallo (Journal of Wildlife, 2023)
Ethiopia is one of the countries found in the eastern horn of Africa, which is endowed with beautiful landscape and topography from which diverse habitats and fauna composition. The objective of this paper is to review relevant documents on distribution of protected area and large-sized mammals order in Ethiopia. The Method of the data were by compiling related information from different sources like published articles grey literature and other office reports from concerned institutions. Altitudinal and geographical variations made the Ethiopia to be among the biodiversity-rich nations in the world. Mammal fauna in Ethiopia consists of 326 species, among 144 genera, 43 families and 14 orders; out of which 32 mammals of the country categories under critically threated group. Among the mammals in Ethiopia eight of them are endemic. Among mammals’ antelopes are flagships (charismatic). The large mammals are mainly concentrated in the south and southwest border.
Keywords: Biomes; Ecosystem’s systems; Mammals distribution; protected area.